Barriers and facilitators to the uptake of tuberculosis diagnostic and treatment services by hard-to-reach populations in countries of low and medium tuberculosis incidence: a systematic review of qualitative literature. Issue 5 (May 2017) - de Vries, Sophia G; Cremers, Anne L; Heuvelings, Charlotte C; Greve, Patrick F; Visser, Benjamin J; Bélard, Sabine; Janssen, Saskia; Spijker, René; Shaw, Beth; Hill, Ruaraidh A; Zumla, Alimuddin; van der Werf, Marieke J; et al.
Summary: Tuberculosis disproportionately affects hard-to-reach populations, such as homeless people, migrants, refugees, prisoners, or drug users. These people often face challenges in accessing quality health care. We did a systematic review of the qualitative literature to identify barriers and facilitators to the uptake of tuberculosis diagnostic and treatment services by people from hard-to-reach populations in all European Union (EU), European Economic Area, EU candidate, and Organisation for Economic Co-operation and Development countries. The 12 studies included in this review mainly focused on migrants. Views on perceived susceptibility to and severity of tuberculosis varied widely and included many misconceptions. Stigma and challenges regarding access to health care were identified as barriers to tuberculosis diagnosis and treatment uptake, whereas support from nurses, family, and friends was a facilitator for treatment adherence. Further studies are required to identify barriers and facilitators to the improved identification and management of tuberculosis in hard-to-reach populations to inform recommendations for more effective tuberculosis control programmes.